GAMBARAN FAKTOR PREDISPOSISI IMPAKSI SERUMEN PADA SISWA SMP DI WILAYAH KERJA PUSKESMAS BANDARHARJO (Overview of The Predisposing Factors to The Cerumen Impaction of Junior High School Students in Bandarharjo Health Center Working Area) - Fina Khiliyatus Jannah; Lintang Dian Saraswati; Muyassaroh Muyassaroh; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Cerumen impaction can generally be prevented, one of the way is to know the risk factors. Limited data on both the patient suffered from cerumen impaction and the research of its risk factors in Indonesia make it important to pay more attention to the case. This study aims at showing the overview of the predisposing  factors of  the cerumen impaction of Junior High School Students in Bandarharjo Health Center Working Area.Observational analytic study with cross sectional study design. The research was conducted by using questionnaires, interviews, measurements of BW and BH, and the cerumen examination. Samples are taken by using simple random sampling method with the amount of 110 respondents of Junior High School Students in Bandarharjo Health Center Working Area.Based on the data, 62% of the respondents did not suffer from cerumen impaction, while 38% others suffered from cerumen impaction. The level of knowledge of up to 54,5% of the respondents is quite good. The respondents who suffered from cerumen impaction have poor ear cleaning behavior (60,5%).The amount of respondents who did not suffer from cerumen impaction is larger than those who suffer. Most of the respondents has such good knowledge, good ear cleaning behavior, obese-ranged Body Mass Index (BMI), moderate physical activity, and suffering stress.